Marketing Mix–Based Strategies for Enhancing School Competitiveness: A Case Study of SMK Ma’arif NU 1 Ajibarang - Nabila, Nizar; Hanif, Muh. (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to analyze the implementation of the marketing mix strategy and its contribution to the competitiveness of educational institutions at SMK Ma’arif NU 1 Ajibarang. The research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and documentation involving key informants, including school leaders, teachers, and students’ parents. Data analysis was conducted using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results show that the implementation of the marketing mix strategy at SMK Ma’arif NU 1 Ajibarang encompasses seven elements (7Ps), namely product, price, place, promotion, process, physical evidence, and human resources. The product aspect is reflected in the diversity of study programs, extracurricular activities, the BTA program, the culture of Qur’anic recitation, and the role of alumni. The price aspect is demonstrated through the provision of scholarships and affordable education costs. The place aspect is supported by the school’s strategic location. Promotion is carried out through direct socialization, the kirka system, and support from the Nahdlatul Ulama community. The process aspect is realized through close engagement with the community and the implementation of student discipline, while physical evidence and human resources are supported by adequate facilities and infrastructure as well as teacher development programs. These marketing strategies contribute to strengthening the institution’s image, increasing public interest, building trust and loyalty among parents, creating differentiation and competitive advantage, and encouraging stability as well as growth in student enrollment...